Coronary Artery Bypass Grafting in Sulaymaniyah: A Retrospective Analysis of the Rate and Outcome in One-Year - Abdulsalam Y Taha; Bawar Abubakr Mohammed; Mohammed Omer Salim; Shadyar Omer Faraj (Basrah Journal of Surgery, 2024)
Background Coronary artery disease (CAD) is a very common disease with its incidence steadily rising worldwide. The study aims to show our experience in management of CAD using coronary artery bypass grafting (CABG). Methodology This retrospective study enrolled all patients who underwent CABG surgery in Sulaimani during 2023 whose medical files could be accessed. The patients were operated upon in Sulaimani Cardiac Hospital (SCH) (Public) and Anwar Sheikha Medical City (ASMC) (Private). Patients’ medical files were reviewed, pertinent data was entered into a Microsoft Access database and the results were analyzed and statistically tested thereafter. Results CABG accounted for 59.2% of total procedures. The patients' ages ranged from 35 to 81 years, with a mean age of 59.6, and the majority were males (76.9%). The top risk factors were hypertension (55.8%) and diabetes mellitus (48.5%). Common symptoms included chest pain (72.3%) and dyspnea (53.1%). Most patients had multivessel CAD (89.0%) and a normal ejection fraction (74.7%). CABG was the primary procedure in 91.3%, accompanied with other surgeries in 8.7%, with mitral valve surgery being the most common additional procedure (5.9%). The study noted that left internal mammary artery (LIMA) and great saphenous vein (GSV) were the main grafts used. Majority (88.5%) of patients experienced no complications post-surgery, with median sternotomy wound infection being the most common complication. The average hospitalization period was 4.48 days, longer in private hospitals than in public ones. The study reported a 2.7% mortality rate within 30 days, which was significantly higher in the public hospital, among females, and those with lower preoperative ejection fractions. Prior PCI and concomitant surgeries had no statistically significant impact on the mortality. Conclusions CABG surgery is a time-tested safe and effective therapy for CAD. The annual rate, complications and mortality of CABG in this series were comparable to other studies.